Critical, Logical & Creative Thinking in A Reflective Classroom Practices - Suciana Wijirahayu; Hendro Priyatmoko; Siti Hadianti (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
This study examines the application of higher order thinking in a class of Word Formation in Modern English course in Faculty of Classical and Modern Philology, Sofia University. The course description, classroom activities and assessment are presented to give evidence on how high order thinking was applied by the lecturers. The experience of taking courses in Language and Culture program, Department of English and American Studies, implemented in the four language skills from the courses of Varieties of Spoken English and The Principle of Literary Analysis are also elaborated. In the English classrooms, the students were asked to apply higher order thinking skills in order to improve their English mastery. Deep understanding about the subject matters and being able to construct pedagogical content knowledge to develop higher-order thinking skills of the students were shown in the classroom practices in this study.